ROLE OF MAGNETIC FIELD AND DENSITY GRADIENTS IN RAYLEIGH-TAYLOR INSTABILITY OF LASER PRODUCED PLASMAS - Ayub, M. K.; Mahmood, S. (The Nucleus, 2020)
Hydrodynamic equations of laser produced plasmas are presented and solved to calculate the linear growth rate of Rayleigh-Taylor instability (RTI) by using normal mode analysis. The growth rates of RTI are calculated in the absence and presence of the external magnetic field. The growth rates are presented graphically against the perturbation wavelength for different angles between the wave vector and initial horizontally directed magnetic field. The dependence of RTI growth rate on the interface density gradient and ablation effects is also investigated. It is found that growth rate of RTI is decreased in the presence of magnetic field; interface density gradient and ablation effects in laser produced plasmas. The numerical results are also presented and found to be in good agreement with the experimental observations.